Accuracy of Potassium Supplementation of Fluids Administered Intravenously. (9th April 2015) - Hoehne, S. N.; Hopper, K.; Epstein, S. E.
<x xml:space="preserve">Abstract</x> Background Potassium (K+) supplementation of isotonic crystalloid fluids in daily fluid therapy is commonly performed, yet its accuracy in veterinary medicine is undetermined. Objective To investigate the accuracy of K+ supplementation in isotonic crystalloid fluids. Animals None. Methods Observational study. 210 bags of fluid supplemented with KCl being administered to hospitalized dogs and cats intravenously (IV) were sampled over a 3‐month period. Measured K+ concentration ([K+]) was compared to the intended [K+] of the bag. In a second experiment, 60 stock fluid bags were supplemented to achieve a concentration of 20 mmol/L K+, mixed well and [K+] was measured. In another 12 bags of 0.9% NaCl, K+ was added without mixing the bag, and [K+] of the delivered fluid was measured at regular time points during constant rate infusion. Results The measured [K+] was significantly higher than intended [K+] (mean difference 9.0 mmol/L, range 6.5 to >280 mmol/L, P < .0001). In 28% of clinical samples measured [K+] was ≥5 mmol/L different than intended [K+]. With adequate mixing, K+ supplementation of fluids can be accurate with the mean difference between measured and intended [K+] of 0.7 (95% CI −0.32 to 1.7) mmol/L. When not mixed, K+ supplementation of 20 mmol/L can lead to very high [K+] of delivered fluid (up to 1410 mmol/L). Conclusions and Clinical Importance Inadequate mixing following K+ supplementation of fluid bags can lead to potentially life threatening IV infused [K+]. Standard protocols for K+ supplementation should be established to ensure adequate mixing.